A Multicenter Assessment of Anatomic Suitability for Iliac Branched Devices in Eastern Asian Patients With Unilateral and Bilateral Aortoiliac Aneurysms - Li, Zheyun; Zhou, Min; Wang, Guili; Yuan, Tong; Wang, Enci; Zhao, Yufei; Shu, Xiaolong; Zhang, Yuchong; Lin, Peng; Fu, Weiguo; Wang, Lixin (Frontiers in Cardiovascular Medicine, 2022)
Objective: This study aims to assess the suitability of four types of commercial iliac branch device systems to treat Eastern Asian abdominal aortic aneurysm (AAA) patients with bilateral or unilateral common iliac artery aneurysms (CIAAs). Methods: Patients with a coexisting AAA and a unilateral or bilateral CIAAs who underwent endovascular aneurysm repair (EVAR) at two tertiary centers in China from 2014 to 2018 were reviewed. Morphology of lesions was measured and the anatomic suitability for Cook iliac branch device (IBD), Gore iliac branch endoprosthesis (IBE), Lifetech iliac branch stent graft (IBSG), and Jotec IBD was evaluated according to the latest instructions for use. Results: Seventy-six patients with AAA were enrolled, including 35 bilateral CIAAs, 41 unilateral CIAAs. A hundred and eleven lesions were investigated aggregately: 16.2%, 28.8%, 21.6%, and 19.8% met the criteria for Cook IBD, Gore IBE, Lifetech IBSG, and Jotec IBD, respectively. A total of 34 (44.7%) patients could be treated for at least one lateral lesion. The diameter of the internal iliac artery (IIA) was the most common restriction for IBD application. Additionally, the IIA diameter of lesions in the bilateral group was significantly larger compared with the unilateral group (P < .001). Based on the anatomical characteristics alone, it is more likely that IBDs will benefit unilateral lesions than bilateral ones (P < .05). However, there was no difference between the suitability for patients with unilateral or bilateral CIAAs (P >.05). Conclusions: Less than half of Eastern Asian patients with aortoiliac aneurysms were eligible for IBD application. This was primarily due to the IIA diameter failing to meet the criteria. And thus, the suitability of lesions in bilateral group was significantly lower than that in the unilateral group. Aiming to optimized the design of the next generation iliac branch devices, IIA diameter and the anatomical characteristics of the bilateral lesions should be considered deliberately.